An Investigative Study of the Literature of Japanese Zen Buddhism and Crime Control - Niwantha, Haputhanthrige Pathum (Journal of Advanced Research in Humanities and Social Sciences; Vol 11 No 1 (2024): Journal of Advanced Research in Humanities and Social Sciences, 2024)
This research paper presents an investigative study of the literature on Japanese Zen Buddhism and its potential role in crime control. Japanese society has a unique cultural and religious landscape, which includes the presence of Zen Buddhism as a significant spiritual and philosophical tradition. This study seeks to explore the historical context of Japanese Zen Buddhism, its key principles, and its potential influence on crime control in Japan. By conducting a comprehensive literature review, we aim to examine the principles of Zen Buddhism that emphasize mindfulness, self-awareness, and non-violence, and assess how these principles may be applied to crime prevention and control. The study also investigates the historical and contemporary interaction between Zen Buddhism and crime control in Japan. To address these objectives, a multi-faceted research approach is employed. First, we delve into the historical development of Japanese Zen Buddhism and its philosophical foundations. We then explore the principles and practices of Zen Buddhism that may be conducive to crime control and rehabilitation. Through case studies, interviews with Zen practitioners, and an analysis of crime rates in areas with Zen temples, we evaluate the potential impact of Zen Buddhism on crime control. Furthermore, this research examines the integration of Zen meditation and rehabilitation programs in correctional facilities and their effectiveness in reducing recidivism. Ethical considerations in conducting research on religion and crime control are also addressed. The findings of this study reveal the potential of Japanese Zen Buddhism as a positive influence on crime control, emphasizing the importance of mindfulness, self-reflection, and non-violence in preventing and reducing criminal behaviour. The implications of this research extend to the fields of criminal justice, rehabilitation, and social policy. By fostering a better understanding of the relationship between Zen Buddhism and crime control, this study contributes to a broader conversation on holistic approaches to crime prevention.